2020
DOI: 10.1021/acsami.9b22687
|View full text |Cite
|
Sign up to set email alerts
|

Electroforming-Free, Flexible, and Reliable Resistive Random-Access Memory Based on an Ultrathin TaOx Film

Abstract: A flexible resistive switching (RS) memory was fabricated on a Ta/TaO x /Pt/polyimide (PI) structure with various TaO x thicknesses (5, 10, and 15 nm). The oxygen vacancy (V O ) concentrations in the TaO x films were also adjusted by controlling the oxygen partial pressure during TaO x deposition to obtain different electroforming (EF) behaviors. When the devices of Ta/TaO x / Pt/PI showed the EF-free characteristic, the reliability and endurance performance were greatly improved compared to those of devices w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Previous study reported that the resistance of the device showed dependence on the device size. [22,40] The resistance of device decreased as the device size decreased, which is consistent to our measurement in Figure S5a, Supporting Information. In addition, smaller memory window (R OFF /R ON ) of bigger device was observed under similar filament condition (Figure S5b, Supporting Information).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Previous study reported that the resistance of the device showed dependence on the device size. [22,40] The resistance of device decreased as the device size decreased, which is consistent to our measurement in Figure S5a, Supporting Information. In addition, smaller memory window (R OFF /R ON ) of bigger device was observed under similar filament condition (Figure S5b, Supporting Information).…”
Section: Resultssupporting
confidence: 88%
“…The results in Figure S4c,e, Supporting Information, agreed with Figure 1b, indicating the consistent distribution of oxygen vacancies. [22,38] From the peak deconvolution of XPS spectra in Figure S4d-f, Supporting Information, it was found that the Ta 2 O 5 contained considerable amounts of oxygen defects, partial lattice oxygen, and surface absorbed oxygen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2(d), nearly 10 3 NL (V read ¼ 1.5 V, 1/2V read ¼ 0.75 V) can be achieved in the integrated 1S1R cell, which signicantly reduced half-selected cells' leakage current. 27,33 Fig. 1 Besides the non-linear selection, our device also shows uniform resistive switching characteristics.…”
Section: Methodsmentioning
confidence: 86%
“…The memristors based on Ta/TaO x system shows excellent electrical characteristics, such as high endurance (more than 10 11 ), fast speed (10 ns), low switching energy (sub 110 nJ), analogue switching. [25][26][27][28] And the non-linear selector devices based on TaO x have been reported before. [29][30][31] However, a single device based on Ta/TaO x system with coexistence of stable resistive switching and uniform non-linear selection has not yet been reported and a clear physical explanation of this mechanism is still lacking.…”
Section: Introductionmentioning
confidence: 99%